(untitled) (Academia Science Repository, 2023)
Taxation of individuals is an important source of revenue for governments worldwide. However, there are several issues and challenges associated with the taxation of individuals. This annotation provides a review of the literature on the problems of taxation of individuals and their improvement over the years. The review finds that the key issues related to taxation of individuals include complexity, fairness, compliance, and enforcement. The literature also suggests various ways to address these issues, such as simplifying tax codes, introducing progressive taxation, providing better taxpayer education, and using technology to improve compliance and enforcement. Additionally, there is a growing interest in alternative approaches to taxation, such as environmental taxation and tax incentives for social goals. The review concludes that there is a need for policymakers to balance the objectives of revenue generation and fairness in taxation and explore innovative solutions to improve the taxation of individuals.